Obra de arte x obra-de-arte: um olhar sobre a cisão entre a engenharia e a arquitetura em uma perspectiva filosófico-histórica da arte - Antunes, Vera Regina Gomes Luduvice (2010)
This paper intends to show the engineers vision while diving into the world of art, to try to understand the historical and philosophical aspects that differentiate the classification of work of art of engineering and architecture. The path of enlightenment about the meaning of the final work of engineer and architect came from a study on the concept of work of art in the conception of such writers as T. Adorno, H. Gadamer, W. Benjamin H. Jauss, even belonging to different lines of thought converge on the character interpretative of art. The social division of work was relevant and extremely interest in research on the conceptual distinction between the design of the architect executed in his studio and the construction site, main local of action of the engineer. Such differences led to study of aesthetic and realize the invisibility that seems to involve the engineers work. Going through the history could analyzed the academic background that go through the future professionals interested in careers devoted to engineering and architecture and, therefore, to understand the ideologies that surround the two professions.